KAPABILITAS PENGURUS BUMDES PERMATA DALAM MENGELOLA UNIT USAHA DI DESA KAMPUNG BARU SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2023 - S, Al-fajri; Pane, Rico Purnawandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
BUMDes (Village-Owned Enterprises) Permata plays an important role in the village economy. However, in its implementation, BUMDes Permata faces challenges in terms of financial record-keeping, accountability, and oversight, which have not been adequately addressed. This affects the capability and operational performance of BUMDes Permata in carrying out activities in accordance with Government Regulation No. 11 of 2021. This study aims to analyze the implementation of financial record-keeping, accountability, and oversight at BUMDes Permata, as well as to determine the extent to which operational standards are implemented in accordance with applicable regulations, particularly Government Regulation No. 11 of 2021. The research method used is qualitative, with descriptive data analysis. The type of data used includes primary data obtained from research informants and secondary data from related documents. The research was conducted at the BUMDes Permata office in Kampung Baru Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency, from 2021 to 2023. The research results show that BUMDes Permata is not yet fully capable in terms of individual, organizational and business entity capacity. Based on Technical Skills, limited training efforts and lack of mastery of modern technology and structured accounting applications are obstacles. In Human Skills, even though there are communication and collaboration efforts, the interpersonal skills of management still need to be strengthened. Meanwhile, in Conceptual Skills, even though the understanding of organizational structure and business unit planning is good, there needs to be an increase in evaluation and system development to increase the management capacity of BUMDes in the future. Keywords: Capability, BUMDes, Village Enterprises